BRANDMORPHOSIS THEORY: How Brands Evolve and Adapt - Wijaya, Bambang Sukma (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2012)
The journey, change, evolution, and metamorphosis of a brand's life can be read through a biographical narrative approach called Brandmorphosis. Thus, Brandmorphosis is a description of the journey, evolution, and metamorphosis of a brand's life which is studied from three important dimensions, namely narrative, transformative, and retrospective. In every story, there is always a dynamic plot, setting, characters, conflict, and climax/anti-climax. Several aspects in the narrative dimension, including Brand Story, Brand Genre, Brand Settings, Brand Characters, Brand Conflicts, and Brand Climax/Anti-Climax. From this story (narrative dimension) we can read the romance of a brand's life struggle from surviving, dodging, rising, falling, sliding smoothly to tripping over various obstacles, rising again, succeeding, failing, and other stories. From a change (transformative dimension) we can know when, how, and why the change occurred or was carried out, what new value is offered from the change, and how its impact. For that, aspects in the transformative dimension are Brand Reformation (rejuvenating, re-branding/rebranding, reincarnating, and revitalizing) and Brand Expansion (extending, proliferating, corporatizing). Meanwhile, from a reflection (retrospective dimension), we can reflect on important, historic, influential, and unforgettable moments in life. Therefore, aspects in the retrospective dimension include Historic Moments, Heroic Moments, Dramatic Moments, and Turning-point Moments. Of course, those moments carry a special meaning, awaken, remind, and give new energy for the next life journey.  TEORI BRANDMORFOSIS: Bagaimana Merek Berevolusi dan Beradaptasi Perjalanan, perubahan, evolusi dan metamorfosis hidup merek pun dapat dibaca melalui pendekatan naratif biografis yang dinamakan Brandmorphosis. Dengan demikian, Brandmorphosis adalah gambaran perjalanan, evolusi dan metamorfosis hidup merek yang dikaji dari tiga aspek penting yakni narasi, transformasi, dan retrospeksi.  Dalam setiap cerita, selalu ada plot, latar, karakter, konflik dan klimaks/antiklimaks yang bersifat dinamis. Maka beberapa aspek dalam dimensi naratif, di antaranya Brand Story, Brand Genre, Brand Setting, Brand Characters, Brand Conflicts, dan Brand Climax/Anti-Climax. Dari cerita (narasi) ini kita dapat membaca romantika perjuangan hidup merek dari bertahan, berkelit, naik, turun, meluncur mulus hingga tersandung berbagai rintangan, bangkit lagi, sukses, gagal, dan  kisah-kisah lainnya. Dari perubahan (transformasi) kita dapat mengetahui kapan, bagaimana dan kenapa perubahan itu terjadi atau dilakukan, nilai baru apa yang ditawarkan dari perubahan itu, dan bagaimana dampaknya. Untuk itu aspek-aspek dalam dimensi transformative adalah Brand Reformation (rejuvenating, re-branding/rebranding, reincarnating, revitalizing) dan Brand Expansion (extending, proliferating, corporatizing). Dari renungan (retrospeksi), kita dapat bercermin pada momen-momen penting, bersejarah, berpengaruh dan tak terlupakan dalam hidup.  Sehingga aspek-aspek dalam dimensi retrospektif mencakup Historic Moments, Heroic Moments, Dramatic Moments, dan Turning-point Moments. Momen-momen itu tentu membawa makna khusus, menyadarkan, mengingatkan, dan memberi energi baru untuk perjalanan hidup selanjutnya. To cite this article (7th APA style):Wijaya, B. S. (2012). Brandmorphosis Theory: How Brands Evolve and Adapt. Journal Communication Spectrum, 2(2), 215-225